HBR at 100 : the most influential and innovative articles from Harvard Business Review's first century. (Harvard Business Review Press, 2022)
"Harvard Business Review is the foremost destination for smart management thinking. Now, at its 100th anniversary, this commemorative volume brings together the most influential ideas since its inception. With thought leaders including Michael E. Porter, W. Chan Kim and Renee Mauborgne, Rosabeth Moss Kantor, Peter Drucker, and Clayton M. Christensen, this book puts HBR's greatest concepts at your fingertips. HBR at 100 curates twenty of HBR's bestselling articles of all time on key topics such as leadership, strategy, innovation, entrepreneurship, and more. With an introduction by Harvard Business Review Editor-in-Chief Adi Ignatius and additional bonus content, you'll learn how these groundbreaking ideas continue to be relevant in today's business context-and what to keep in mind as you prepare for the future. Whether you're a longtime reader or you're picking up an HBR volume for the first time, this book offers all you need to understand the most critical ideas in management-and set yourself and your organization up for success"--